INFLUENCE ON DIFFERENT RATES OF NITROGEN AND POTASSIU FERTILIZERS APPLICATION ON YIELD AND YIELD CONTRIBUTING CHARACTERS OF RICE (Oryza sativa L.) - Oo, Nway; Ngwe, Kyaw; Win, Theingi; Myo, Lu Zaw (AGPE THE ROYAL GONDWANA RESEARCH JOURNAL OF HISTORY, SCIENCE, ECONOMIC, POLITICAL AND SOCIAL SCIENCE, 2024)
To evaluate the effect of different rates of nitrogen and potassium fertilizers on yield and yield contributing characters of rice and to compare the effect of N and K balanced fertilization on the growth and yield of rice production. The pot and field experiments were conducted at Yezin Agricultural University farm, Zeyarthiri Township, Nay Pyi Taw in the dry and wet season of 2022-23. Using T1 (control),T2(86 kg N ha-1+ 92 kg K ha-1),T3(86 kg N ha-1+ 46 kg K ha-1),T4(46 kg N ha-1+ 92 kg K ha-1 ), T5 (46 kg N ha-1+ 92 kg K ha-1),T6(129 kg N ha-1+92 kg K ha-1),T7(129 kg N ha-1+46 kg K ha-1) in seven treatments with three replications included in the experiment using a randomized complete block design (RCBD). According to the experimental results, different applications of N and K had significant effects on plant height, number of tillers, number of panicles, panicle length, number of spikelets and grain yield and revealed significant differences in grain yield in response to N and K applications. These findings found that combined different applications of N and K gave the highest grain yield from T6 (45.2 g plant-1) in dry season (pot experiment) and (6.2 t ha-1) in wet season (field experiment)), which statistically from all other N and K differed application treatments. Based on the results, the combined effect of N and K fertilizer treatments gave a higher grain yield, an increased yield percentage, and better growth performance. Therefore, the combined use of N and K fertilizer treatments gave higher grain yield, yield increase percentage and better growth performance.